Periapical Status and Quality of Root Canal Obturation in Elderly Population: A Systematic Review - Silva, Fabrício Rutz da; Hebling, Eduardo; Cândido Brizon, Valéria Silva; Pereira, Antônio Carlos; Padilha, Edna Zakrzevski; Hintz, Raisa (Journal of Orofacial Research, 2014)
The aim of this study was to investigate the relationship between root fillings and the presence of apical periodontitis in studies with samples containing elderly patients. The data were obtained by means of a systematic review of studies that evaluated the quality of root fillings and their relationship with periapical health. 1,376 potentially relevant articles were selected, of which 667 were repeated and 16 were duplicates. 693 abstracts were analyzed, with 608 of these being excluded and 85 selected for reading in full. Fourteen (14) articles were included, totaling data of 135,566 teeth. Of these, 13,704 (10.1%) had endodontic fillings, with 6,455 (47.1%) being considered adequate and 7,249 (52.9%) inadequate. Among the teeth with apical periodontitis, 2,084 (32.3%) had adequate endodontic fillings and 3,749 (51.6%) had inadequate fillings. There was a significant correlation between the quality of endodontic fillings considered adequate and lower frequency of apical periodontitis in elderly patients.